2017
DOI: 10.1021/acschemneuro.6b00356
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Iron(II) Preferring Dopamine Agonist Chelator as Potential Symptomatic and Neuroprotective Therapeutic Agent for Parkinson’s Disease

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder, and development of disease-modifying treatment is still an unmet medical need. Considering the implication of free iron(II) in PD, we report here the design and characterization of a novel hybrid iron chelator, (-)-12 (D-607) as a multitarget-directed ligand against PD. Binding and functional assays at dopamine D/D receptors indicate potent agonist activity of (-)-12. The molecule displayed an efficient preferential iron(II) chelation proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 51 publications
4
26
0
Order By: Relevance
“…This was further validated in a cell-based lipid peroxidation assay where pre-treatment with the compound was found to significantly reduce iron (II) induced lipid peroxidation. Our results also demonstrated D-607 to be much more neuroprotective in this experimental model versus pramipexole and a 8-hydroxyquinoline-derived Fe(III) preferring dopamine agonist, thereby, reflecting contribution of the bipyridyl moiety in enhanced neuroprotection (Das et al, 2017). …”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…This was further validated in a cell-based lipid peroxidation assay where pre-treatment with the compound was found to significantly reduce iron (II) induced lipid peroxidation. Our results also demonstrated D-607 to be much more neuroprotective in this experimental model versus pramipexole and a 8-hydroxyquinoline-derived Fe(III) preferring dopamine agonist, thereby, reflecting contribution of the bipyridyl moiety in enhanced neuroprotection (Das et al, 2017). …”
Section: Discussionsupporting
confidence: 55%
“…Our previous iron binding study revealed far higher specificity for complex formation of D-607 with Fe(II) compared to Fe(III). This study also indicated a neuroprotective effect of D-607 in neuronal PC12 cells against iron (II)-induced cell death (Das et al, 2017). The fact that compound D-607 was able to rescue these cells strongly indicated the ability of selective intracellular complexation of Fe(II) by the compound to reduce oxidative stress.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations